IMPACT OF LOCAL RECURRENCE ON PATIENTS WITH BREAST CANCER DIAGNOSIS SUBMITTED TO CONSERVATIVE SURGERY AT HOSPITAL PÚBLICO DO SERVIDOR ESTADUAL - Cabral, Samira Marcondes; Antonini, Marcelo; Vasconcelos, Raissa Naiara Barros; Cardoso, Mariana Soares; Solino, Matheus de Paula (Mastology, 2021)
Introduction: Breast cancer is a major cause of mortality in Brazil and worldwide. It is a heterogeneous disease with specific molecular subtypes, which are associated with different prognosis and responses to treatment. Objectives: The present study aimed at assessing the incidence of local recurrence in patients undergoing conservative surgery and its impact on overall survival. As a secondary outcome, there are the prognostic factors of local recurrence in addition to the relationship with systemic metastasis. Methods: It is a retrospective cohort including 500 patients submitted to conservative surgical treatment, from March 2014 to March 2019 at Hospital do Servidor Público Estadual de São Paulo. Results: The results are compatible with the literature, with local recurrence in 4% of patients and more relapses with triple-negative subtype; 367 patients had hormonal treatment: five (1.4%) relapsed and 51 patients did not use hormonal treatment, four (7.8%) relapsed. This shows a higher percentage of recurrence in the group without adjuvant hormone therapy when compared to the group that underwent treatment (p=0.016); 7.4% of patients developed metastasis, which was more prevalent in patients diagnosed with triple-negative subtype cancer and pure Her. This group had an estimated probability of survival significantly lower (72.3%) than the group without metastases (98%) (p<0.001). In this cohort, disease-free survival was 93.4% and overall survival was 96% over a median of three years of follow-up. Other prognostic factors, established in the literature, such as age, lymph node involvement, tumor size, in addition to systemic treatment and radiotherapy had no significant difference between patients who did or did not relapse. Conclusion: In this cohort, patients diagnosed with breast cancer and who underwent conservative surgery, evolving with local recurrence, did not present a higher risk of death, and we found tumor biology as a risk factor for locoregional recurrences. Patients who evolved with systemic metastases showed a reduction in the overall survival rate.